Harnessing Liposome Interactions With the Immune System for the Next Breakthrough in Cancer Drug Delivery - La-Beck, Ninh M.; Liu, Xinli; Wood, Laurence M. (Frontiers in Pharmacology, 2019)
Liposomal nanoparticles are a heterogeneous group of engineered drug carriers that have tremendous therapeutic potential in the treatment of cancer. They increase tumor drug delivery, significantly attenuate drug toxicity, and protect the drug from degradation. However, two decades after approval of the first nanoparticle-mediated anticancer drug, pegylated liposomal doxorubicin (Doxil), there has yet to be a major shift in cancer treatment paradigms. Only two anticancer nanoparticles are used in the first-line treatment of cancer patients, with all others relegated to the refractory or salvage setting. Herein, we discuss new insights into the mechanisms underlying in vivo interactions between liposomes and the tumor immunologic milieu, and the knowledge gaps that need to be addressed in order to realize the full clinical potential of cancer nanomedicines. We also discuss immunopharmacology insights from a parallel field, Cancer Immunotherapy, which have the potential to generate breakthroughs in Cancer Nanomedicine.